ALAT PAKAN KUCING OTOMATIS BERBASIS INTERNET OF THINGS (IOT) MENGGUNAKAN TELEGRAM DAN MIKROKONTROLLER WEMOS D1 R1 - Reiski Ndalusandi P. (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
Irregular feeding is often a problem for people who have busy work with their work, resulting in a lack of attention to feeding, it will also have an impact on animal health if the keeper is too busy to not be able to feed the animals on time. Therefore it must be made an automatic feeding device that can be adjusted according to certain hours so that animal keepers no longer need to worry about their pets, an HC-SR04 Ultrasonic sensor is needed which functions to detect the distance of the availability of feed in the storage container, if the condition of the feed in the storage container is still full, the Servo Motor rotates to open the cover in the storage container and the RTC DS3231 is also added which works as a timer for feeding. Wemos D1 R1 microcontroller as a processor and sender of data to the telegram application so that animal keepers can set feeding hours. The final result obtained from the manufacture of this tool is the creation of an automatic feeding device that can provide convenience to animal keepers when they are busy at work.